EFFECT OF VITAMIN D SUPPLEMENTATION DURING PREGNANCY AND ITS OUTCOMES FOR MOTHER AND CHILD - Dr. Shazia Baloch; Dr. Rabia Iram; Dr. Aisa Sharif; Dr. Nargis Taj; Dr. Firdous Ara; Dr. Maryam Shoaib (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Vitamin D, a vital micronutrient, plays a crucial role in various physiological processes, including bone health, immune function, and cellular regulation.Objectives: The main objective of the study is to find the effect of Vitamin D supplementation during pregnancy and its outcomes for mother and child. Material and methods: This prospective study was conducted at Sandeman Provincial Hospital Quetta from June 2023 to December 2023. Baseline data on maternal characteristics, including age, parity, BMI, and socioeconomic status, were collected at enrollment. Maternal blood samples were obtained at regular intervals during pregnancy to assess serum vitamin D levels.Results: Data was collected from 180 pregnant females. In the supplementation group (n=90), participants had a mean age of 28.02 years (± 4.56), slightly younger than the control group (n=90) with a mean age of 29.98 years (± 5.09). At baseline, both groups exhibited similar levels of vitamin D status, with mean levels of 15.1 ng/mL (± 3.02) in the supplementation group and 14.9 ng/mL (± 3.45) in the control group. In the supplementation group, maternal outcomes showed lower incidence rates compared to the control group, with 10% experiencing gestational diabetes compared to 15%, 8% experiencing preeclampsia compared to 12%, and 7% experiencing preterm birth compared to 10%. Neonatal outcomes also favored the supplementation group, with infants having higher birth weights (mean of 3.2 kg ± 0.3) compared to the control group (mean of 3.0 kg ± 0.4) and higher Apgar scores at 1 minute (mean of 9.2 ± 0.5 compared to 8.8 ± 0.6).Conclusion: It is concluded that Vitamin D deficiency during pregnancy is widespread and has garnered increasing concern in the past decade, primarily due to its nonclassic actions, which contribute to various maternal and neonatal complications.